Presentation of macro and micro design of implants for use in oral implantology - Rudolf, Rebeka; Zorko, Lidija; Anžel, Ivan (Anali PAZU, 2022)
The development of techniques in oral implantology is connected closely to the macro and micro design of the implant´s surface. This is, namely, the final phase which is crucial for quality of bonding between the implant and the surrounding bone. In this paper are presented the problems which are connected on building and stability maintenance of the system after incorporation of the implant into the oral environment. The implant possibility is, namely, connected with the acceptance and transfer of stresses on the bite surfaces.
Keywords: implantology; macro and micro design of surface; osteo- integration process; Ti alloys